ENHANCED SOLUBILITY OF NON-STEROIDAL ANTI-INFLAMMATORY DRUGS BY HYDROXYL TERMINATED S-TRIAZINE BASED DENDRIMERS - M. PATEL, RINKESH; N. PATEL, HEMA; G. GAJJAR, DHAVAL; M. PATEL, PRAVINKUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: To synthesize and characterized s-triazine based dendrimer generations fromN,N'-bis(4,6-dichloro-1,3,5-triazin-2-yl)hexane-1,6-diamine as core. To use dendrimer generation (G1-G3) as solubility enhancers of Ketoprofen, Ibuprofen, and Diflunisal and to study effects of factors such as pH, concentration of dendrimer and generation number on solubility of NSAIDS. Methods: s-triazine based dendrimer was synthesized up to generation 3 by divergent method. Synthesized dendrimer generations were characterized by IR, 1H-NMR, 13C-NMR, ESI-Mass spectrometryand elemental analysis. Candidature of full generation triazine based dendrimers (G1-G3) as solubility enhancers of NSAIDS were investigated by Higuchi and Connors method at different dendrimer concentrations, pH and generations. Results: Dendrimer was synthesized up to generation 3 and structures of dendrimer generations were confirmed by IR, 1H-NMR, 13C-NMR and ESI-Mass spectrometry. Dendrimer significantly enhances solubility of NSAIDS by either hydrophobic interaction or hydrogen bonding or both. Conclusion: Synthesized triazine based dendrimers (G1-G3) enhances solubility of NSAIDs in water. Solubility of NSAIDS increased with increase in concentration of the dendrimer, pH and dendrimer generation.Â  The order of solubility of NSAIDS was found to be Ketoprofen> Ibuprofen >Diflunisal by dendrimer. Keywords: triazine trichloride, dendrimer, Nonsteroidal Anti-Inflammatory Drugs, solubility enhancers